Usage of N-TB Mobile Application to Evaluate the Nutritional Status of Pulmonary TB Patients erolled under Nikshay Poshan Yojana Scheme at Ramanagara District, Karnataka – A Cross Sectional Study - Yatnatti, Santosh K; A R, Manasa; Jayram, Sushma; Nagaraja, Sharath Burugina; Mattoo , Sanjay Kumar; S, Anil; Anjum, Shazia; DM, Narayanaswamy (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2023)
Introduction: Tuberculosis affects millions of people every year, and India is among the 30 countries with the highest TB burden as identified by the WHO, accounting for 87% of worldwide cases. The significant role of nutrition in the treatment of TB has been well established. Various strategies and innovations have been introduced globally to combat TB, hastening the process towards its elimination. One such measure taken by the Indian government is the Nikshay Poshan Yojana (NPY) program, which provides nutritional assistance to individuals affected by TB. Methodology: A cross sectional study with objectives to assess the nutritional status of TB patients using N-TB application and to determine the factors associated with utilization pattern of Nikshay Poshan Yojana was conducted for a period of 6 Months from August 1st 2021 to January 31st 2022. A total of 270 patients with pulmonary TB were selected according to PPPS from 5 different Talukas/ tuberculosis units (TUs) of Ramanagara district who had received incentives for all 6 months of their treatment period and information was collected using a pre-designed, pretested and semi-structural questionnaire. Results: Among 270 study subjects, 143 were underweight at the time of diagnosis. Among 143 underweight study subjects at the time of diagnosis, 31.5% (45) attained normal BMI, and 1.4% (2) became overweight, while the majority 67.1% (96) remained underweight at the end of 6 months of treatment. It was found that there was statistically significant association between nutritional status at the end of 6 months and age group, gender, marital status and presence of co-morbidity. Conclusions: Most of the individuals who took part in the study followed the NPY plan according to its intended purpose. It is crucial to provide NPY promptly before completion of treatment to gain a better understanding of the improved nutritional status. Regular nutritional evaluations and counselling for TB patients would also enhance positive treatment outcomes.